Psycho-sexual characteristics of youths attending a voluntary family life education programme in Ibadan (1995)
Public family life and sex education programmes have remained a rather controversial issue all over the world. The controversy has usually concerned the value base on which such programmes are designed, as well as the value base of those who will deliver the programmes; and therefore, the psychosocial and moral impact that such programmes may have on their recipients who usually are from different religious, moral or ethical backgrounds. In order to overcome these misgivings, an annual public and voluntary family life education programme was developed in Ibadan based on free, multiple but individually clear value based, as the ethical and religious background of the attenders indicate. The socio-demographic characteristics and the attitudes and practices of the youths in relation to two of the topics covered in the 1991 programme- drugs and sexual intercourse are reported in this paper. Reported sexual experience among the youths was 18.4% with an indication that regardless of previous experience, 65.5% of them would want to limit sexual intercourse in the future to marriage only. Experience of the youths